Religion and local politics in Southern Europe: a research agenda - Giorgi, Alberta (2016)
This article brings to a conclusion the series of three special sections published in 2015 and 2016 by Religion, State and Society on ‘Religion and local politics in southern Europe’. We set up a research agenda on the interactions between religion and local politics in Southern Europe. In doing so, we focus on the localisation of religion, including religious debates, and on the impact of the recent economic crisis. More specifically, we address the local as a contested concept, the multilevel governance of religion as a scalar opportunity structure – in relation to the transnational dimension of religious actors – the effects of such changes in the welfare landscape and the impact of the economic crisis on the activities and strategies of religious actors in Southern Europe. Our research agenda focuses on the interactions between two main dimensions: the territorial impact of political and economic changes, and the multiscalar schemes of territorial governance.